First Record of Rhynchotherium blicki (Frick, 1933) for the Late Cenozoic of Costa Rica - Alberto Laurito Mora, César (2005)
The genus Rhynchotherium has been described as a fossil for the Upper Miocene of Guatemala and volcanic deposits of Nicaragua, the Upper Miocene and Pliocene fluvial sediments of El Salvador and Honduras, but this is the first time it is recorded from Costa Rica. The material described includes a partially preserved skull with three upper molars. The material has been collected from a single locality, Santa Rita, near San Vito Town in the Puntarenas Province.